2021
DOI: 10.1039/d1cp03587h
|View full text |Cite|
|
Sign up to set email alerts
|

Interfacial acidity on the strontium titanate surface: a scaling paradigm and the role of the hydrogen bond

Abstract: A fundamental understanding of acidity at an interface, as mediated by structure and molecule-surface interactions, is essential to elucidate the mechanisms of a range of chemical transformations. While the strength...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…There are several lines of thought to address this question: this observation is consistent with Sr being a weaker Lewis acid than Ti as reported by Chapleski et al 10 According to their results, TiO 2 - and SrO-terminated surfaces differ in Lewis-acid character because Ti carries a higher partial charge than Sr with the consequence that 2-propanol binds more strongly by 0.49 eV on STO(100) terminated with TiO 2 than on STO(100) terminated with SrO. In another recent work, 9 adsorption microcalorimetry was utilized to characterize the surfaces of SrTiO 3 with CO 2 and NH 3 .…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…There are several lines of thought to address this question: this observation is consistent with Sr being a weaker Lewis acid than Ti as reported by Chapleski et al 10 According to their results, TiO 2 - and SrO-terminated surfaces differ in Lewis-acid character because Ti carries a higher partial charge than Sr with the consequence that 2-propanol binds more strongly by 0.49 eV on STO(100) terminated with TiO 2 than on STO(100) terminated with SrO. In another recent work, 9 adsorption microcalorimetry was utilized to characterize the surfaces of SrTiO 3 with CO 2 and NH 3 .…”
Section: Resultssupporting
confidence: 83%
“…The extent of deprotonation of 2-propanol follows the earlier established surface acidity order of the perovskites STO(100). 9,10 The Lewis acidity and extent of deprotonation are as follows: SrO-STO(100) (negligible Lewis acidity) < off-the-shelf STO(100) < TiO 2 -STO(100). 9 A comparison of thin film TiO 2 with TiO 2terminated STO(100) indicates that Sr in STO(100) increases Ti′s Lewis acidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Co 3 O 4 nanospheres with a preferential (110) surface orientation were also studied by Falk et al 16 They reported full conversion and 100% selectivity for 2-propanol oxidation to acetone at 430 K. In contrast to the theoretical finding for (001) surface orientation, they suggested a preferential Mars-van Krevelen mechanism for the (110) surface. 16 Recently, Roy and coworkers performed a DFT study of 2-propanol adsorption on strontium titanate (STO) 17 and found three geometries for molecular adsorption of rather similar binding energy.…”
Section: Introductionmentioning
confidence: 99%